Experimental and Analytical Investigation for the Responses of Semi-Submersible Platform - Ng , C.Y. (2010)
This paper presents the results of model tests of an offshore semisubmersible platform subjected to regular sea waves that was conducted in the wave tank of the offshore engineering laboratory at Universiti Teknologi PETRONAS. The measured responses were compared with the numerical results obtained by using time domain analysis and linear wave diffraction analysis. The semi-submersible platform prototype was modeled as a rigid body with three degrees of freedom restrained by mooring lines. In the time domain analysis, Linear Airy wave theory and Morison modified equation were used for calculating the wave forces on the structure. The mass, damping and stiffness matrices were evaluated at every time step and the equations of motion were formulated for the platform dynamic equilibrium. The equations were solved using Newmark Beta time domain dynamic analysis method. The results were obtained as Response Amplitude Operators (RAO) in surge, heave and pitch. Then the RAOs were obtained using software by linear wave diffraction analysis. The wave tank tests responses were compared with the analytical responses and the approaches were validated the applicability on the structures with large hulls e.g. the semisubmersible platforms.